New data on Parasyrisca (Araneae: Gnaphosidae) from Mongolia - Marusik, Yuri M.; Fomichev, Alexander A.; Omelko, Mikhail M. (Zootaxa, 2019)
Three new species of Parasyrisca Schenkel, 1963 belonging to the potanini-group are described from Western Mongolia: P. platnicki sp. n., P. polchaninovae sp. n. and P. szinetari sp. n. Each species description is based on both sexes. Both the male and female of P. platnicki sp. n. possess some copulatory organ characters unknown in other species of the genus. The previously unknown female and the poorly known male of P. khubsugul Ovtsharenko, Platnick et Marusik, 1995 are described and redescribed respectively, the descriptions being based on the specimens found in Arkhangai and Bayankhongor Aimags. The structures of copulatory organs in Parasyrsca potanini-group are briefly discussed.